1989
DOI: 10.1111/j.1464-410x.1989.tb05253.x
|View full text |Cite
|
Sign up to set email alerts
|

Nephrectomy in Renal Carcinoma with Distant Metastasis

Abstract: A total of 96 cases of renal carcinoma with distant metastasis at the time of diagnosis was studied. The patients were classified into 4 groups: Group O (16) in whom nephrectomy was not performed, Group A (51) who died due to carcinoma within 1 year of nephrectomy, Group B (25) who died due to carcinoma 1 to 3 years after nephrectomy, and Group C (4) who survived for 3 years or more after nephrectomy. Six clinical measurements were evaluated: haemoglobin, ESR, alpha 2 globulin, temperature, weight and C reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…We have reported that RCC cells produce interleukin-6 and that elevation of the serum level of interleukin-6 is signifi cantly related to survival of patients with RCC without metastasis, while the serum level of interleukin-6 does not directly correlate to tumor volume and tumor grade [5]. Onishi et al [15] reported supportive results, indicating that short-term survivals were noted in patients with met astatic RCC showing elevation of acute-phase proteins.…”
Section: -supporting
confidence: 55%
“…We have reported that RCC cells produce interleukin-6 and that elevation of the serum level of interleukin-6 is signifi cantly related to survival of patients with RCC without metastasis, while the serum level of interleukin-6 does not directly correlate to tumor volume and tumor grade [5]. Onishi et al [15] reported supportive results, indicating that short-term survivals were noted in patients with met astatic RCC showing elevation of acute-phase proteins.…”
Section: -supporting
confidence: 55%
“…However, there have been reports indicating that, among patients with an acceptable performance status, those who underwent nephrectomy survived significantly longer than those who did not [9]. In predicting the outcome in patients with advanced RCC, favourable factors include a good performance status, single‐organ metastasis, lower tumour grade, lower T stage and two or fewer of the six clinical measurements (anaemia, high ESR, α‐2 globulin increase, fever of unknown origin, weight loss and a positive reaction to CRP) [10,11]. There are many patients who are unable to undergo nephrectomy because of adverse factors and the prognosis in these patients is unfavourable even if treated with interferon or interleukin‐2.…”
Section: Discussionmentioning
confidence: 99%
“…There were no significant background differences between the present groups except for the proportion of patients who showed para‐neoplastic signs, where significantly more patients in the TAE group had such signs. As these para‐neoplastic signs are accepted as important prognostic factors [9,11] we suggest that the therapeutic effect of TAE is not only on the primary lesion but also has general effects in such high‐risk patients, e.g. immunological reactions against the tumour might be induced in the host [16].…”
Section: Discussionmentioning
confidence: 99%
“…1,2 After nephrectomy, 20% to 50% of patients show recurrence, 3,4 and fewer than 5% of those with metastatic disease are alive at 5 years. The lungs (50%), bones (49%), lymph nodes (6%-32%), skin (11%), liver (8%), and brain (3%) are the most frequent sites of clinical metastases.…”
Section: Introductionmentioning
confidence: 99%